A parametric model to identify hydrodynamic bearing wear at a single rotating speed. (January 2021) - Alves, Diogo Stuani; Fieux, Gauthier; Machado, Tiago Henrique; Keogh, Patrick S.; Cavalca, Katia Lucchesi
Abstract: For dynamic systems, fault detection and diagnosis involve the observation of vibration signals. Faults associated with hydrodynamic bearings are one of the most common causes of forced shutdowns in rotating machinery. If it is a wear fault, the bearing clearance is affected changing the rotating system characteristics. Therefore, the time response of a rotating machine subjected to worn hydrodynamic bearings is analysed to observe the vibration behaviour in presence of bearing wear. Spectral analysis is used to understand intact and worn bearing characteristics and to identify wear severity. For the wear, an improved and new parametric model is generated to increase simulation accuracy. The new approach indicates the severity of wear in the studied hydrodynamic bearings. Highlights: An improved three-parameter wear model, with an extra degree of freedom, namely, the wear angular extent, was developed. For mid/high eccentricity journal positions, shallow/longer wear profiles can be as critical as deeper/shorter wear profile. Promising identification of wear severity using a single rotating speed.